2018
DOI: 10.1002/nop2.121
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptives as possible risk factors for postpartum depression: A retrospective study of the food and drug administration adverse event reporting system, 2004–2015

Abstract: AimPostpartum depression is a mood disorder that commonly affects women during the early postpartum period. The objective of this study was to analyse the association of postpartum depression with drugs (including contraceptive devices and implants) with spontaneously reported adverse events reported in the US Food and Drug Administration Adverse Event Reporting System database.DesignRetrospective study.MethodReports of postpartum depression events between 2004–2015 were analysed with a reporting odds ratio (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
(56 reference statements)
0
14
0
1
Order By: Relevance
“…Secondly, certain types of contraceptives such as hormonal ones increase the risk of developing PND. 22 However, we did not inquire about the type and duration of contraceptive use, and we cannot ascribe the study findings to this relationship. Future studies need to fill these gaps.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Secondly, certain types of contraceptives such as hormonal ones increase the risk of developing PND. 22 However, we did not inquire about the type and duration of contraceptive use, and we cannot ascribe the study findings to this relationship. Future studies need to fill these gaps.…”
Section: Discussionmentioning
confidence: 90%
“…21 Because the symptoms of PND might have started before delivery, screening should also be done during antenatal care visits. 22 , 23 As this was a study conducted in only one healthcare facility and employed a screening tool, a study with a bigger sample size using a diagnostic tool is needed to provide a clearer picture of the prevalence of PND and its related factors in South African primary care.…”
Section: Discussionmentioning
confidence: 99%
“…, pre-pregnancy BMI(Bertone-Johnson et al, 2008;Ertel et al, 2017;LaCoursiere et al, 2010) (Bertone-Johnson et al, 2008Ertel et al, 2017;LaCoursiere et al, 2010), self-perceived stress(Gao et al, 2009;Gollenberg et al, 2010;Ruyak et al, 2016), smoking(Bertone-Johnson et al, 2008;Chen et al, 2019;Quelopana et al, 2011) and oral contraceptive use(Horibe et al, 2018;Roberts and Hansen, 2017;Yonkers et al, 2005), should be fully considered when assessing the association of interest. If welldesigned studies confirm the significant association between pre-pregnancy PMS and development of PPD, history of PMS should be additionally incorporated in the checklist which is currently used by clinical practitioners during antenatal check-ups and/or postpartum visits to screen women at risk of PPD (Centre of Perinatal Excellence, 2017; US Preventive Services Task Force, 2019).…”
mentioning
confidence: 99%
“…An analysis of the development of mood disorders found a higher incidence with POCs but a lower incidence with COCs (Svendal et al 2012). A study of postpartum depression as a reported adverse drug reaction showed higher rates for levonogestrel, etonogestrel, sertraline, and drospirenone (Horibe et al 2018). A study of postpartum DMPA versus CuIUD use showed significant increases in depression scores and major depressive episodes with DMPA (Singata-Madliki et al 2016).…”
Section: Psychological Effectsmentioning
confidence: 99%